Gd(iii) complex of a monophosphinate-bis(phosphonate) DOTA analogue with a high relaxivity; Lanthanide(iii) complexes for imaging and radiotherapy of calcified tissues - Vitha, Tomás; Kubícek, Vojtech; Kotek, Jan; Hermann, Petr; Vander Elst, Luce; Muller, Robert N; Lukes, Ivan; Peters, Joop A (Dalton transactions (Cambridge, England, 2009)
A new phosphinic-acid DOTA-like ligand, DO3AP(BP), containing a geminal bis(phosphonic acid) moiety as a highly effective bone-seeking group, was synthesized in high yield. Its crystal structure was determined by X-ray analysis. Complexation with lanthanide(iii) ions occurs under mild conditions (pH = 8-9, 25 degrees C, 2-3 h). (1)H, (31)P, and (17)O NMR spectroscopy show that DO3AP(BP) forms nine-coordinated lanthanide(iii) complexes with one water molecule in the first coordination sphere except for Ln = Er-Lu, which have in addition a species without lanthanide(iii)-bound water. Selective formation of only two diastereomers (out of four possible) suggests that the coordinated phosphinate phosphorus atom occurs exclusively in one of the enantiomeric forms. The ratio of the twisted square antiprism (TSA) and square antiprism (SA) diastereomers changes along the lanthanide series; the gadolinium(iii) complex has about 35% of the TSA species. The bis(phosphonate) moiety remains free for anchoring to osseous tissue. The (1)H longitudinal relaxivity of the Gd-DO3AP(BP) complex (r(1) = 7.4 s(-1) mM(-1), 20 MHz, 25 degrees C, pH = 7.5) is unexpectedly high compared to that of other monohydrated chelates of similar size thanks to a significant contribution from the second hydration sphere. The water residence time tau(M)(298) is 198 ns. Further increase in the relaxivity was observed in the presence of Zn(ii), Mg(ii) or Ca(ii) ions, due to formation of coordination polymers. Slowing down of the tumbling rate of the Gd-DO3AP(BP) complex upon adsorption on hydroxyapatite also leads to an increase of the relaxivity (r(1) = 17 s(-1) mM(-1), 20 MHz, 25 degrees C, pH = 7.5).
Keywords: Diagnostic Imaging; krystalografie rentgenová; kosti a kostní tkáň; chelátory; Organophosphonates; kontrastní látky; Durapatite; molekulární struktura; gadolinium; Molecular Structure; radiografie; Chelating Agents; kalcinóza; Calcinosis; Crystallography, X-Ray; Lanthanoid Series Elements; Contrast Media; Heterocyclic Compounds, 1-Ring; organofosfonáty; hydroxyapatit; Gadolinium; lanthanoidy; diagnostické zobrazování; Bone and Bones; Radiography; heterocyklické sloučeniny monocyklické